Lulu in the sky : a daughter of Cambodia finds love, healing, and double happiness - Ung, Loung (New York, NY : Harper Perennial, 2012)
"When readers first met Loung Ung in her critically acclaimed memoir First They Killed My Father, she was a young, innocent child in Cambodia. But forced by the Khmer Rouge into the life of a child soldier, she soon found herself locked in a desperate struggle for survival in Cambodia's notorious killing fields. In Lucky Child, her life took a turn. As a refugee in Vermont, she grappled with post-traumatic stress, cultural assimilation roadblocks, and the abandonment of her sister in Cambodia. Now, Lulu in the Sky tells the next chapter in Ung's life, revealing her daily struggle to keep darkness and depression at bay while she attends college and falls in love with Mark Priemer, a Midwestern archetype of American optimism. Lulu in the Sky is the story of Ung's tentative steps into love, activism, and marriage-- a journey that takes her to a Cambodian village to reconnect with her mother's spirit, to a vocation focused on healing the landscape of her birth, and to the patience and unconditional support of a very special man" -- p. [4] of cover.
Concluding the trilogy that started with the bestselling memoir First They Killed My Father, Loung Ung describes her college experience and her first steps into adulthood, revealing her struggle to reconcile with her past while moving forward towards happiness. After the violence of the Khmer Rouge and the difficult assimilation experience of a refugee, Loung's daily struggle to keep darkness, anger, and depression at bay will finally find two unexpected allies: the empowering call of activism, and the redemptive power of love. Lulu in the Sky is the story of Loung's journey to a Cambodian village to reconnect with her mother's spirit; to a vocation that will literally allow her to heal the landscape of her birth; and to the transformative influence of a supportive marriage to a loving man....Loung Ung illuminates her struggle to reconcile with her past while moving forward toward happiness. When readers first met Loung Ung in her critically acclaimed memoir First They Killed My Father, she was a young, innocent child in Cambodia. But forced by the Khmer Rouge into the life of a child soldier, she soon found herself locked in a desperate struggle for survival in Cambodia's notorious killing fields. In Lucky Child, her life took a turn. As a refugee in Vermont, she grappled with post-traumatic stress, cultural assimilation roadblocks, and the abandonment of her sister in Cambodia. Now, Lulu in the Sky tells the next chapter in Ung's life, revealing her daily struggle to keep darkness and depression at bay while she attends college and falls in love with Mark Priemer, a Midwestern archetype of American optimism. Lulu in the Sky is the story of Ung's tentative steps into love, activism, and marriage--a journey that takes her to a Cambodian village to reconnect with her mother's spirit, to a vocation focused on healing the landscape of her birth, and to the patience and unconditional support of a very special man."--Publisher's website.
Prologue: Amah Chiem La Aw (grandmother who possesed good blood): Kompong Speu, Cambodia, January 2000 -- Love. Born of Kambu: Cambodia, 1975-1979 -- Crush: Burlington, Vermont, August 1990 -- Fish sauce and prahok: Colchester, September 1990 -- A good aunt:Essex, autumn 1990 -- To speak or not to speak?: of worms and walls: Battery Park, October 1990 -- No Rapunzel: Shelburne, November 1990 -- Klutz and midirection: Manchester, December 1990 -- Lulu in the sky: Champlain Mill, April 1991 -- A message in Ma Po Tofu: Chapel of Saint Michael's, spring 1991 -- Cupid's evil twin: Fort Ethan Allen, May 1991-- Healing. The long and winding road: Vermont, Maine, and Washington D.C. 1993-1997 -- The girl in the mirror: Washington D.C. May 1887 -- Birthdays: Capitol Hill, June 1997-- A new path: Dupont Circle, D.C. July 1997 -- Cow teats and five hundred high school boys: Washington D.C., September 1997 -- Never silent: Scott Circle, D.C., April 1998 -- Lifelines: Washington D.C. May 1998 -- Exorcist of the writing kind: D.C. and Cambodia, June 1998-February 1999 -- Millennium: Orlando Florida, December 1999 -- Double happiness. Srok Khmer: Kompong Speu, January 2000 -- Khsae family line: Kompong Speu, January 2000 -- Fear of landing: Kompong Speu, January 2000 -- Khmer Inheritance: Oudong, February 2000 -- Somewhere in time: Kompong Speu, February 2000 -- The hills of the poisonous trees: Phnom Penh, February 2000 -- A white giant Barang on the village: Phnom Penh, March 2000 -- A gathering to heal lost souls: Siem Reap, March 2000 -- Double happiness: Vermont, August 2002.
Includes: P.S., insights, interviews & more.
Includes bibliographical references (p. [327]-330).
Keywords: Ung, Loung; Cambodian -- History -- 1975-1979 -- Biography; Refugees -- Biography -- United States; Cambodia -- Biography